The Dynamics of The China Maritime Militia Conflict In South China Sea On Sovereignty Indonesian Countries And ASEAN Region Countries - Jefferson Benyamin; Hikmat Zakky Almubaroq (Faculty of Social Science, Universitas Negeri Padang, 2021)
The South China Sea is a strategic water area and is rich in natural resources. The South China Sea dispute is the hottest dispute in the 21st century, in which China and most ASEAN members are involved indirectly. China's unilateral claim of ownership of the South China Sea area using the nine dash line principle and maritime power has triggered a response from surrounding countries, including Indonesia. For Indonesia itself, its main concern in this conflict is to maintain the security of its country and protect the vulnerable island of Natuna. In this study, we will discuss the dynamics of the China Maritime Militia conflict in the South China Sea against the sovereignty of the Indonesian state and ASEAN countries. This study uses a qualitative method with a literature study approach where the data sources used are journals, articles, books and other relevant sources. Based on the results of the study, it was concluded that the disputes that occurred in the South China Sea were disputes between countries, because the actors were not only claiming countries but also other countries with an interest in the region. Therefore, the strategy taken in efforts to resolve the China Maritime Militia dispute in the South China Sea is to strengthen the capacity of maritime security enforcement and command for various Indonesian maritime law enforcement agencies, and take a free and active approach that is manifested in support and participation in regional organizations such as ASEAN